Enzymatic Synthesis of Acylphloroglucinol 3‐C‐Glucosides from 2‐O‐Glucosides using a C‐Glycosyltransferase from Mangifera indica. Issue 17 (10th March 2016) - Chen, Dawei; Sun, Lili; Chen, Ridao; Xie, Kebo; Yang, Lin; Dai, Jungui
Abstract: A green and cost‐effective process for the convenient synthesis of acylphloroglucinol 3‐ C ‐glucosides from 2‐ O ‐glucosides was exploited using a novel C ‐glycosyltransferase (MiCGTb) from Mangifera indi ca. Compared with previously characterized CGTs, MiCGTb exhibited unique de‐ O ‐glucosylation promiscuity and high regioselectivity toward structurally diverse 2‐ O ‐glucosides of acylphloroglucinol and achieved high yields of C ‐glucosides even with a catalytic amount of uridine 5′‐diphosphate (UDP). These findings demonstrate for the first time the significant potential of a single‐enzyme approach to the synthesis of bioactive C ‐glucosides from both natural and unnatural acylphloroglucinol 2‐ O ‐glucosides. Abstract : One enzyme, one product : A novel C ‐glycosyltransferase from Mangifera indica is reported, which is a promiscuous catalyst that synthesizes bioactive C ‐glucosides from natural and unnatural acylphloroglucinol 2‐ O ‐gulcosides in one‐pot reactions. High yields of C ‐glucosides were achieved even with a catalytic amount of uridine 5′‐diphosphate. This study demonstrates for the first time the significant potential of a single‐enzyme approach for the C ‐glycodiversification.